The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1017/s0007114508199445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-calcium diets with different whey proteins on weight loss and weight regain in high-fat-fed C57BL/6J mice

Abstract: The aim of the study was to compare the effect of different whey protein-containing high-Ca diets on weight loss and weight regain in a model of diet-induced obesity. Obesity was induced in C57BL/6J mice with a high-fat (60 % of energy) diet. Weight loss by energy restriction was performed on four different high-Ca diets (1·8 % CaCO 3 ) containing different whey proteins (18 % of energy): a-lactalbumin (ALA), b-lactoglobulin (BLG), lactoferrin (LF) and whey protein isolate (WPI). After 7 weeks of energy restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 26 publications
4
58
0
1
Order By: Relevance
“…24 Lactoferrin, lactoalbumin, and lactoglobulin may play important roles in weight reduction and the improvement of hyperlipidemia. 25 Because the formula food that contained SP also contained 9 g of MP, further experimental studies will be needed to determine the appropriate dose of MP. An increased consumption of milk has been reported to reduce BMI.…”
Section: Formula Food With Soy Protein Vs Milk Proteinmentioning
confidence: 99%
“…24 Lactoferrin, lactoalbumin, and lactoglobulin may play important roles in weight reduction and the improvement of hyperlipidemia. 25 Because the formula food that contained SP also contained 9 g of MP, further experimental studies will be needed to determine the appropriate dose of MP. An increased consumption of milk has been reported to reduce BMI.…”
Section: Formula Food With Soy Protein Vs Milk Proteinmentioning
confidence: 99%
“…In further support for a role for lactoferrin in reducing adiposity, it has been shown in vitro that this whey protein specifically inhibits adipogenesis and lipid accumulation in adipocytes [31,32]. Although Pilvi et al study showed that β-lactoglobulin was the least effective whey protein for inducing weight loss and for preventing weight gain [30], Pichon et al found that β-lactoglobulin (55% energy) causes the least weight gain when supplemented in a diet containing only fat providing 45% of energy in comparison to a diet containing 35% and 10% energy from carbohydrates and fat or in a diet with 15% and 30% energy from the same macronutrients, respectively [11]. The data again highlights the importance of macronutrient composition on whey proteins effects on energy balance.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Because there were no differences in food intake between the groups, the data suggests a food intake-independent effect of glycomacropeptide on lipid metabolism (fat content) in these animals. With the view to assessing how other whey proteins, namely α-lactalbumin, β-lactoglobulin and lactoferrin may influence body weight and body fat content in rodents, Pilvi et al subjected high fat diet induced obese mice to a 70% energy restricted diet containing whey protein isolate or each of the whey proteins mentioned above (18% energy) for a period of 7 weeks to induce weight loss [30], and subsequently allowed ad libitum access to the diets for further 7 weeks to allow weight gain. Results suggest that α-lactalbumin is the most beneficial whey protein in terms of causing fat loss when provided as part of an energy restricted diet or fed ad libitum.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…reduction of triglyceride absorption, inhibition of the formation of foam cells by impairment of the uptake of the oxidised form of HDL cholesterol by macrophages, inhibition of deposition of fat cells, and involvement in glucose metabolism by increasing insulin sensitivity (2). In their investigations, Pilvi et al (30) and Ibrahim (17) have demonstrated that lactoferrin inhibits formation of fat cells by inhibition of the formation of adiponectin, i.e. a precursor of fat tissue growth.…”
Section: Tab 2 Effects Of Colostrum and Lactoferrin On Tomographic mentioning
confidence: 99%